Analisis Peran Masyarakat Dan Pemerintah Dalam Melestarikan Kerajinan Tanggui di Kelurahan Kuin Cerucuk Kota Banjarmasin - Rochgiyanti, Rochgiyanti; Apriati, Yuli; Azkia, Laila; Mattiro, Syahlan; Rizqullah, M. Yasari; Namira, Namira (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Tanggui is a typical cultural product of the Banjar tribe who live in a wetland environment. Until now, the existence of tanggui can still be found among the Banjar tribe. Although the tanggui is still used by some people in South Kalimantan Province, the interest of the younger generation to preserve the tanggui craft is decreasing. Whereas tanggui is one of the cultural products of the Banjar community, which is full of local wisdom values. This study aims to determine the role of the Kuin Cerucuk Village community and the Banjarmasin City Government in preserving the tanggui craft as a cultural product of people living in a wetland environment. In this study, a qualitative method was used, because there are still problems that need to be explored related to the role of the community and the Banjarmasin City Government in preserving the tanggui craft. This research was conducted in Tanggui Village located in Kuin Cerucuk Village, West Banjarmasin District, Banjarmasin City. The informants in this study totaled 20 people, consisting of tanggui craftsmen who are members of the Bahagia 2 Joint Business Group (KUBE). Determination of data sources was done purposively. Data collection techniques were conducted through interviews, observations, document studies, and audiovisual data to increase the validity of the research. The results of qualitative data collection in the form of interview recordings, interview transcripts, observation notes, written documents, photographs, and other notes, were tested for validity through a triangulation process. The validated data were then reduced, presented, and conclusions were drawn. The results show that the role of the Kuin Cerucuk Village community is carried out by preserving the nipa plant ecosystem, and internalizing how to make tanggui crafts to the younger generation. The role of the Banjarmasin City government can be seen from the regulatory policies issued and their implementation in an effort to preserve the tanggui craft . From the results of the study it can be concluded that the role of the community and the Banjarmasin City Government is very significant in preserving the tanggui craft . The implication of this research is that the tradition of making tanggui crafts as a cultural product of the community in the wetland environment can be preserved.